2022
DOI: 10.3390/gels8020133
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Topical Nano-Lipid-Based Delivery of Butenafine: In Vitro Characterization and Antifungal Activity

Abstract: The present research work was designed to prepare butenafine (BN)-loaded bilosomes (BSs) by the thin-film hydration method. BN is a sparingly water-soluble drug having low permeability and bioavailability. BSs are lipid-based nanovesicles used to entrap water-insoluble drugs for enhanced permeation across the skin. BSs were prepared by the thin-film hydration method and optimized by the Box–Behnken design (BBD) using lipid (A), span 60 (B), and sodium deoxycholate (C) as independent variables. The selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Moreover, the sustained drug release was observed after 10 h up to 24 h. In the first 6 h of the in vitro drug release, as shown in Figure , slower drug release from complex-loaded liposomes over the CUR-loaded liposomes was observed, and it may be attributed to the complex formation that may cause slower drug release. Furthermore, it is supported with the published literature. , The in vitro drug release kinetics on multiple models were investigated, and it was observed that the first-order model ( R 2 = 0.9991) was the best fit for CUR-GO-loaded liposomes (shown in Table ). The drug release model revealed that the drug release exponent occurred because of the non-Fickian diffusion process, which is often observed to be n > 0.5 and is fitted into the first order .…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Moreover, the sustained drug release was observed after 10 h up to 24 h. In the first 6 h of the in vitro drug release, as shown in Figure , slower drug release from complex-loaded liposomes over the CUR-loaded liposomes was observed, and it may be attributed to the complex formation that may cause slower drug release. Furthermore, it is supported with the published literature. , The in vitro drug release kinetics on multiple models were investigated, and it was observed that the first-order model ( R 2 = 0.9991) was the best fit for CUR-GO-loaded liposomes (shown in Table ). The drug release model revealed that the drug release exponent occurred because of the non-Fickian diffusion process, which is often observed to be n > 0.5 and is fitted into the first order .…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, it is supported with the published literature. 27 , 31 The in vitro drug release kinetics on multiple models were investigated, and it was observed that the first-order model ( R 2 = 0.9991) was the best fit for CUR-GO-loaded liposomes (shown in Table 2 ). The drug release model revealed that the drug release exponent occurred because of the non-Fickian diffusion process, which is often observed to be n > 0.5 and is fitted into the first order.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations